Assessment of the Master of Nursing Science Program In Nursing Administration, Improvement Version, AD 2013 - Chaiphibalsarisdi, Puangtip; Lertsakornsiri, Maleewan; Jamjan, Laiad; Laoopugsin, Suwannee; Anusanti, Suwanna; Chusri, Dares (Journal of The Royal Thai Army Nurses, 2020)
This mixed method research with CIPP model approach, aimed to explore the opinions of 1) policy and program administrators, 2) nursing directors, 3) alumni, 4) teachers, 5) students’ supervisors and students’ colleagues, and 6) students. There were 33 sample. The measurement consisted of 4 parts; test for environment, test for input, test for process, and test for product. The content and statistical analysis were being performed. The results of the study were as follows; 1) The nursing administration program is still needed but must design the curriculum to allow learners have the required competency. 2) For results of the input, the students had highest satisfaction on measurement and evaluation that were congruent with the curriculum and study activities at private and international settings. The lowest satisfaction was the number of teachers who had provided consultation covering various fields. 3) In the process assessment, the teachers were able to provide teaching-learning experiences in accordance with the philosophy and objectives of the curriculum. However, the consultation in conducting the thesis/thematic paper, the teacher must be thorough in research process and must be able to respond to individual student’s needs. 4) For the product of the curriculum, the overall competency and the behavior of the students towards their professional responsibilities were at a very g